Gangs and Special Laws Dealing with Gang Crimes in India: Understanding the characteristics and repercussions of gang crimes in India (Journal of Advances and Scholarly Researches in Allied Education, 2017)
A coordinated crime is one in which at least two persons work together in a systematic mannerto carry out a protest. It is usually carried out by gang members or members of an affiliation who assistone another and commit crimes together. As a result, it tends to be a group of individuals with a companywhose main goal is to make money is to get revenue via illegal activity. Because these protests are carriedout by a group of individuals, they are sometimes referred to as gang crimes or organised crimes. In thiscase, organised crime refers to a group of generally outstanding families that form a mafia to commitcrimes. Coordinated Crime has the following characteristics. Their illegal protests are usuallyconspiratorial in nature. They plan or actually carry out atrocities that have a violent and terrifying toneto them. Despite the fact that they submit activities that are clearly illegal, the path is very difficult. Theyare very meticulous, efficient, and methodical. They defend their authority against direct involvement incriminal activity. They are very well-liked by the general people and often engage in legislative debates.Usually, their purpose was to do anything unlawful. Economic gain is the ultimate purpose of every gangcrime. This may be obtained by a variety of means, including narcotics, gambling, loan sharking, andmoney laundering.